How a Developing Country Faces COVID-19 Rehabilitation: The Chilean Experience - Torres-Castro, Rodrigo; Neculhueque-Zapata, Ximena; Hrzic-Miranda, Katherina; Gutiérrez-Arias, Ruvistay; Valenzuela-Suazo, Raúl; Castro-Acuña, Cristobal; Ríos-Quevedo, Marianela; Águila-Villanueva, Camilo; Seron, Pamela (Frontiers in Public Health, 2022)
The coronavirus 19 (COVID-19) pandemic has been one of the most significant challenges to public health in recent decades. The heterogeneity of government responses and the varying preparedness of health systems has determined that the pandemic's impact differs from country to country. Chile is no stranger to the challenges posed by rehabilitation in a developing country. We aimed to describe the approach to rehabilitation during the pandemic in Chile in the public health system since rehabilitation is considered a relevant health strategy from the prevention to management of complications, mitigation of sequelae, or new complications associated with COVID-19. For this, a descriptive study was conducted on the rehabilitation strategies implemented by Chile to respond to the COVID-19 pandemic. The analysis includes the context of the Chilean health system and the matrix of access to rehabilitation services in COVID-19. The Health Ministry (MINSAL) rehabilitation strategy includes five central axes: approaches, specific lines, transversal lines, intervention, and funding. Additionally, the policies were based and supported by the WHO recommendations. Intensive care unit beds were increased approximately 68%, and the primary care response was the reconversion of function depending on the epidemiological context. During the 2021-2022 period, the estimated number of people diagnosed with a post-COVID-19 condition was 80,528. With this, we can conclude that a developing country has managed to coordinate a rehabilitation policy for people with COVID-19 by generating a structure of the different health system levels. However, the effectiveness of this policy will need to be evaluated in the future.